Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.1292/jvms.67.75
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Susceptibility of Mannheimia haemolytica Isolates from Cattle in Japan from 2001 to 2002

Abstract: ABSTRACT. A total of 27 clinical isolates of Mannheimia haemolytica from cattle in Japan from 2001 to 2002 were examined for antimicrobial susceptibility to 25 antimicrobial agents. The minimum inhibitory concentrations of 25 different antimicrobials were determined by an agar dilution method according to the guidelines of the National Committee for Clinical Laboratory Standards. Of the 27 isolates, seven isolates (26.9%) were resistant to at least one of the 25 drugs and resistance rates ranged from 3.7 to 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
12
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 11 publications
3
12
1
Order By: Relevance
“…Seventy-two percent of M. haemolytica isolated in this study were antimicrobial resistant, about twice the percentage detected for M. haemolytica isolated from the nasopharynx of cattle displaying BRD (35%) in a previous study from our group (19). Furthermore, evidence for multidrug resistance against more than three antimicrobials was found in 45% of the isolates collected during this project, results agreeing with reports that multidrug resistance in BRD pathogens is on the increase (35)(36)(37).…”
Section: Discussionsupporting
confidence: 91%
“…Seventy-two percent of M. haemolytica isolated in this study were antimicrobial resistant, about twice the percentage detected for M. haemolytica isolated from the nasopharynx of cattle displaying BRD (35%) in a previous study from our group (19). Furthermore, evidence for multidrug resistance against more than three antimicrobials was found in 45% of the isolates collected during this project, results agreeing with reports that multidrug resistance in BRD pathogens is on the increase (35)(36)(37).…”
Section: Discussionsupporting
confidence: 91%
“…In Japan, enrofloxacin (ERFX) was first approved for bovine pneumonia in 1991, and three fluoroquinolone compounds have been approved for bovine pneumonia to date. Our previous study showed that all 27 isolates of M. haemolytica were susceptible to fluoroquinolones during the period of 2001 to 2002 [1]. However, we observed emergence of fluoroquinolone-resistant M. haemolytica in 2004 in our surveys (unpublished data).…”
contrasting
confidence: 42%
“…The breakpoints of ABPC, CEZ, CP, GM, KM, NA and TMP were adopted to the same breakpoints by NCCLS guidelines [15]. The breakpoints of CL, DSM, OTC and ERFX have been described in our previous report [9]. Bacteriophage typing was performed according to the methods of the Public Health Laboratory Service (PHLS), London, United Kingdom [1].…”
mentioning
confidence: 99%